Immunohistochemical study of RhoC GTPase in oral squamous cell carcinoma - Martins, L H B; Pinheiro, N M; Spina, A M B; Micheletti, A M R; Carboni, S S C M; Crema, V O (Cellular and Molecular Biology, 2015)
Oral squamous cell carcinoma (OSCC) is a disease with high mortality and morbidity. Metastasis is a significant prognostic factor of the OSCC patients. The Rho GTPases are signaling proteins that controls important cellular processes in various complex mechanisms involved in carcinogenesis. This study aimed to evaluate the expression pattern of RhoC in OSCC protein by immunohistochemistry in situ. Immunohistochemical reactions were performed for RhoC by the method of avitina-biotin-peroxidase activity in samples OSCC: well differentiated (BD, n=6), moderately differentiated (MD, n=24) and poorly differentiated (PD, n=13). The morphometry was taken by QuickScore (percentage and intensity of staining) and only intensity staining. There was no statistical difference (p>0.05) through none of the modes of morphometric analysis between BD, MD and PD. And the RhoC staining was not associated with the histopathologic grading (Ï‡2 = 4.65, p>0.05). However, the morphological evaluation of immunostained for RhoC in cases BD, MD, PD OSCC, regardless of histopathologic grading. These results suggest that there is no correlation between the RhoC immunoexpression and histopathological grading of OSCC.